Execution of micro-credentials in Malaysia: the challenges and readiness of higher education leaders / Ahmad Aizuddin Md Rami ... [et al.] - Md Rami, Ahmad Aizuddin; Ismail, Ismi Arif; Sarman, Mohd Amin; Zulkifly, Nurul Afiqah (Universiti Teknologi MARA, 2023)
In Malaysia, higher education institutions (HEI) have made significant efforts to integrate micro-credentials into their educational systems. However, the status of micro-credentials among these institutions remains ambiguous. Furthermore, there is a dearth of comprehensive research on university leaders within the context of public universities in Malaysia. The study was conducted to investigate the challenges and readiness in implementing micro-credentials by university leaders within higher education institutions (HEIs) in Malaysia. The research focused on public universities in Peninsula Malaysia and used a qualitative approach through a case study method. The study involved five informants who were university leaders from these institutions. In summary, this study focuses on the challenges and readiness of university leaders in implementing micro-credentials in Malaysian HEIs. The major themes that emerged from the findings represent these challenges. The study aims to shed light on the importance of university leaders' roles and perspectives in the successful integration of micro-credentials. For data collection and analysis, this study used semi-structured interviews and thematic analysis respectively. The data analysis led to the development of the major themes that emerged from findings include (i) application of micro-credentials, (ii) human resources, (iii) facilities and infrastructures, (iv) accreditation, and (v) accountability, referred to challenges faced by university leaders. By addressing these challenges, university leaders can contribute to the advancement of micro-credentials within the higher education system in Malaysia.